INOVASI PEMBELAJARAN PENULISAN NASKAH DRAMA ANAK DENGAN MENGGUNAKAN STRATEGI IDCD (IDENTIFICATION, DESIGN, CHANGE, DAN DEVELOPMENT) - Fiyan Ilman Faqih (Jurnal Pendidikan Bahasa dan Sastra Indonesia Metalingua, 2020)
The writing children's drama scripts is an underdeveloped skill. This happens because students not understand who children and how characteristic children. One way to solve this problem is to innovate learning strategies. The strategic innovation is IDCD (identification, design, change, and development). This strategy was created for the needs of writing skills, especially writing children's drama scripts for students. Strategies were created to create learning more creative, innovative children's drama script writing, and children's drama scripts that are created according to the child's level of development.